2023
DOI: 10.26650/ase20221208209
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Histopathological Alterations in the Liver and Kidney of Olive Barb (Puntius sarana, Hamilton 1822) as an Indicator of the Surma River’s Pollution

Abstract: Water pollution poses a global hazard to aquatic biota and ecological sustainability, causing a hazard to aquatic organisms such as fish. The aim of this study was to evaluate the impact of toxic chemical contaminants on histopathological biomarkers in the liver and kidney of olive barb (Puntius sarana) collected from the Surma River in comparison to a control group of fish. The histological bio-monitoring assessment involved the sampling of thirty (30) table-sized fish collected from the four-sampling sites (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…They highlight the importance of maintaining suitable temperature conditions in aquatic environments to ensure the well-being and optimal functioning of fish gills, which are critical for their survival and adaptation to changing environmental conditions. This finding is also supported by Saber [93] who investigated the gill tissues of common carp Cyprinus carpio L. where gill sections of this fish species showed marked histological lesions during low and high temperatures, and by Zaman et al [94] who investigated liver and kidney of Puntias sarana and found numerous histopathological changes.…”
Section: Discussionsupporting
confidence: 53%
“…They highlight the importance of maintaining suitable temperature conditions in aquatic environments to ensure the well-being and optimal functioning of fish gills, which are critical for their survival and adaptation to changing environmental conditions. This finding is also supported by Saber [93] who investigated the gill tissues of common carp Cyprinus carpio L. where gill sections of this fish species showed marked histological lesions during low and high temperatures, and by Zaman et al [94] who investigated liver and kidney of Puntias sarana and found numerous histopathological changes.…”
Section: Discussionsupporting
confidence: 53%
“…( 2023 ), Zaman et al. ( 2023 ), and the images were taken by using Optika light microscope, Italy (B9).…”
Section: Methodsmentioning
confidence: 99%
“…The internal organ such as gill, kidney, liver, stomach and skin were taken carefully and perfectly preserved in 10% neutral buffer formalin for making histological slide preparations. The protocol of histological slide preparation during the experiment was followed as outlined by Rahman et al (2023), Zaman et al (2023), and the images were taken by using Optika light microscope, Italy (B9).…”
Section: Histological Slide Preparationsmentioning
confidence: 99%
See 1 more Smart Citation